Preparation method of CPAN-coated ZnO layer for alkali metal interface modification

The CPAN@ZnO layer prepared through electrospinning and annealing technology solves the problems of uneven lithium deposition and dendrite growth during the circulation of lithium metal batteries, improves the balun efficiency and cycle stability of the battery, and reduces production costs.

CN119390108APending Publication Date: 2025-02-07UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411527189.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing lithium metal batteries have problems such as uneven lithium deposition and dendrites during the circulation process, resulting in low efficiency and poor circulation stability. The commonly used interface modification methods use high-cost fluorine-containing materials and are highly uncontrollable. .

Method used

Using the preparation method of CPAN@ZnO layer, PAN, zinc salt and elemental sulfur or metal sulfide mixed solution are made into CPAN@ZnO precursor through electrospinning technology, and annealing process is used to generate a uniform distribution of ZnO and amorphous S. Circularize CPAN@ZnO layer.

Benefits of technology

Effectively improve charge distribution and surface electrostatic potential, promote uniform deposition of lithium, inhibit dendrites, improve the dynamic performance and cycle life of the battery, and reduce production costs and improve controllability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109552180000141
    Figure BDA0005109552180000141
  • Figure BDA0005109552180000151
    Figure BDA0005109552180000151
  • Figure BDA0005109552180000161
    Figure BDA0005109552180000161
Patent Text Reader

Abstract

The invention provides a preparation method of a CPAN-coated ZnO layer, which comprises the following steps: sequentially dissolving PAN, zinc salt, elemental sulfur or metal sulfide in an organic solvent, and then carrying out electrostatic spinning and annealing to prepare the CPAN-coated ZnO layer. Through compounding of PAN, zinc salt and elemental sulfur or metal sulfide, electrostatic spinning is combined with annealing, the CPAN-coated ZnO layer capable of inhibiting dendritic crystal growth, promoting lithium desolvation and inducing uniform deposition of lithium is obtained, after the CPAN-coated ZnO layer prepared by the scheme is used for a battery, the battery dynamic performance (the lithium ion transference number is 0.5-0.8, the lithium ion desolvation rate is 0.5-0.8, the lithium ion desolvation rate is 0.5-0.8, the lithium ion desolvation rate is 0.5-0.8, and the lithium ion desolvation rate is 0.5-0.8) is high. The interface exchange current density is 0.5 mAcm <-2 > to 1.5 mAcm <-2 >; and the cycle life is effectively prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery materials, and in particular to a method for preparing a CPAN@ZnO layer for alkali metal interface modification. Background Art

[0002] The rapid growth of electronic devices such as mobile devices and electric vehicles has driven the rapid development of the global power energy and energy storage market. As a result, higher requirements are placed on the electrochemical performance of lithium metal batteries, especially the cycle life. However, lithium metal is often accompanied by problems such as uneven lithium deposition, lithium dendrite growth, and volume expansion during the cycle process, resulting in low coulombic efficiency and poor cycle stability. Therefore, how to improve coulombic efficiency and cycle stability has become a major research hotspot today. Among them, the method of inducing lithium deposition and inhibiting dendrite growth by interfacial modification of lithium metal has received widespread attention.

[0003] At present, the common means of interface modification is to regulate lithium salts or add film-forming additives to form SEI films. For example, the Chinese patent (CN118281317A) provides a new ester electrolyte formula for lithium metal batteries. By introducing fluorinated carbonate solvent additives, a SEI layer rich in LiF inorganic components is formed at the negative electrode, thereby improving the stability of the lithium negative electrode and stabilizing lithium deposition / stripping. However, most of the modification methods mentioned in the existing public patents use high-cost raw materials containing fluorine, which poses a severe challenge to large-scale commercial applications. In addition, the currently disclosed solutions usually require the formation of a solid electrolyte interface (SEI) during the operation of the battery, which has a large degree of uncontrollability. More importantly, although these patents provide new ideas for battery technology, in actual applications, the cycle life of the battery still has significant room for improvement, which puts higher demands on further research and innovation.

[0004] Therefore, how to obtain a simple and controllable interfacial film that can effectively promote uniform lithium deposition, inhibit lithium dendrite growth and promote lithium desolvation while further improving the battery cycle life has become a focus of current research. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention proposes a method for preparing a CPAN@ZnO layer for alkali metal interface modification, which utilizes polyacrylonitrile (PAN), zinc salt and elemental sulfur or metal sulfide to cooperate with each other, and solves the problems of uneven lithium ion deposition and decreased cycle performance and low coulombic efficiency caused by lithium dendrite growth through electrospinning combined with annealing, thereby effectively improving the cycle life and coulombic efficiency of alkali metal batteries.

[0006] The method for preparing the CPAN@ZnO layer for alkali metal interface modification provided by the present invention is as follows:

[0007] S1: According to the stoichiometric ratio, PAN, zinc salt, elemental sulfur or metal sulfide are dissolved in an organic solvent in sequence, and electrospinning is performed at a voltage of 15kV-30kV, the electrospinning push speed is 0.6mL / h-1.5mL / h, and the collection distance is 15cm-35cm to obtain a CPAN@ZnO precursor;

[0008] S2: Annealing the CPAN@ZnO precursor at 140°C-300°C for 0.1h-2.5h to obtain a CPAN@ZnO layer.

[0009] As a further solution, in step S1, the molecular weight of PAN is selected from any one of 5w, 8.5w, and 15w.

[0010] As a further solution, in step S1, the mass ratio of PAN, zinc salt, elemental sulfur or metal sulfide is (8-12):(1-6):(0.1-2).

[0011] As some preferred schemes, in step S1, the mass ratio of PAN, zinc salt, elemental sulfur or metal sulfide is (9-11): (2-5): (0.5-2).

[0012] As a further solution, the mass ratio of PAN to the organic solvent in step S1 is (4-6): (40-45).

[0013] As a further solution, the zinc salt in step S1 is selected from any one of zinc-based inorganic metal compounds and zinc-based organic metal compounds.

[0014] As a further embodiment, the zinc-based organometallic compound is selected from any one or more of an alkyl zinc compound, an alkoxy zinc compound, an aromatic zinc compound, and a β-diketone zinc compound.

[0015] As a further solution, the metal sulfide in step S1 is selected from any one or more of sodium sulfide, potassium sulfide, calcium sulfide, zinc sulfide, aluminum sulfide, lead sulfide, mercuric sulfide, ferrous sulfide, iron sulfide, copper (I) sulfide, copper (II) sulfide, magnesium sulfide, manganese (II) sulfide, nickel (II) sulfide, cadmium sulfide, cobalt (II) sulfide, thallium (I) sulfide, silver sulfide, and barium sulfide.

[0016] As a further solution, in step S1, the organic solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide.

[0017] As a further solution, in step S1, the electrospinning pushing speed is 0.8 mL / h-1.2 mL / h, the collection distance is 20 cm-30 cm, and the voltage is 18 kV-25 kV.

[0018] As a further solution, the thickness of the electrospun CPAN@ZnO precursor in step S1 is controlled by the volume of a mixed solution of PAN, zinc salt, elemental sulfur or metal sulfide. The volume of the mixed solution of zinc salt, elemental sulfur or metal sulfide is selected from 2mL-10mL, and the thickness of the CPAN@ZnO precursor is selected from 3μm-30μm.

[0019] As a further solution, the volume of the mixed solution of PAN, zinc salt, elemental sulfur or metal sulfide is selected from 4 mL to 8 mL, and the thickness of the electrospun CPAN@ZnO precursor is selected from 5 μm to 20 μm.

[0020] As a further solution, in step S2, the annealing atmosphere is air.

[0021] As a further solution, in step S2, the annealing temperature is selected from 240°C-300°C, and the annealing time is selected from 0.5h-2h.

[0022] This scheme also provides a CPAN@ZnO layer prepared by the above method, with a surface electrostatic potential difference of <0.64KJ / mol and a binding energy greater than 3.5eV.

[0023] This solution also provides a battery comprising an electrode modified with a CPAN@ZnO layer, with a lithium ion migration number of 0.5-0.8 and an interface exchange current density of 0.5 mA cm -2 -1.5mAcm -2 , cycle life>4500h.

[0024] As a further solution, the battery also includes an electrolyte.

[0025] As a further solution, the electrolyte further includes an electrolyte salt, a solvent and an additive.

[0026] As a further embodiment, the solvent is selected from any one of ether solvents, ester solvents and sulfone solvents.

[0027] As a further embodiment, the electrolyte salt is selected from an organic electrolyte salt and an inorganic electrolyte salt.

[0028] As a further solution, the organic electrolyte salt is selected from at least one of sodium sulfonimide salt and lithium sulfonate.

[0029] Compared with the prior art, the present invention has at least the following beneficial effects:

[0030] (1) In the present invention, by combining PAN, zinc salt, elemental sulfur or metal sulfide, an electrostatic spinning method combined with an annealing process is used to generate a cyclized CPAN@ZnO layer with uniform distribution of ZnO and amorphous S, which can effectively improve the charge distribution, uniform surface electrostatic potential, and induce uniform lithium deposition. On the one hand, the presence of the CPAN@ZnO layer can utilize electron-rich functional groups such as -C=C- and -C=N- to attract lithium ions, promote the desolvation of lithium ions, and further improve the kinetic performance of the battery. On the other hand, during the battery cycle, ZnO generates Li-Zn alloy to reduce the reduction potential of lithium ions, while amorphous sulfur generates Li2S to protect the metal negative electrode, improve the cycle stability of the battery, and achieve an ultra-long cycle life of the battery.

[0031] (2) The method provided by the present invention is simple to operate, cost-effective, and easy to implement in subsequent large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0033] Figure 1 Example 1, Tafel performance comparison diagram of Li||Li battery in Comparative Example 1;

[0034] Figure 2 This is a performance comparison diagram of the Li||Li battery in Example 1 and Comparative Example 1;

[0035] Figure 3 The electrochemical performance diagram of the full battery matched with NCM811 in Example 1 and Comparative Example 1;

[0036] Figure 4 A is a comparison diagram of surface electrostatic potential between Example 1 and Comparative Example 3, and B is a schematic diagram of binding energy between PAN, CPAN@ZnO layer, ZnO, DOL and DME and lithium;

[0037] Figure 5 It is the XRD comparison diagram of Example 1 and Comparative Example 3;

[0038] Figure 6 Infrared comparison diagrams of Example 1 before and after annealing and Comparative Example 3 and PAN;

[0039] Figure 7 A is the SEM image of Comparative Example 3, B is the SEM image of Example 1;

[0040] Figure 8 This is the constant voltage polarization curve of Example 1. DETAILED DESCRIPTION

[0041] For ease of understanding, the present invention will be described in more detail below and examples of the present invention are given, but the scope of the present invention is not limited thereby.

[0042] The method for preparing the CPAN@ZnO layer for alkali metal interface modification provided by the present invention is as follows:

[0043] S1: According to the stoichiometric ratio, PAN, zinc salt, elemental sulfur or metal sulfide are dissolved in an organic solvent in sequence, and electrospinning is performed at a voltage of 15kV-30kV, the electrospinning push speed is 0.6mL / h-1.5mL / h, and the collection distance is 15cm-35cm to obtain a CPAN@ZnO precursor;

[0044] S2: Annealing the CPAN@ZnO precursor at 140°C-300°C for 0.1h-2.5h to obtain a CPAN@ZnO layer.

[0045] PAN is a common spinning polymer. The prepared fibers have the characteristics of good flexibility and strong toughness. At the same time, the presence of -CN electron-rich groups on PAN makes it have a strong attraction to positively charged lithium ions, so it can promote lithium desolvation. However, -C≡N on PAN cannot obtain a uniform and ideal lithium deposition effect. One solution is to anneal PAN to make -C≡N undergo a cyclization reaction and transform it into -C=N- with more uniform charge distribution and surface electrostatic potential. However, the cyclization reaction of PAN usually involves the breaking of the -C≡N triple bond and the formation of new bonds. These processes often require higher energy to overcome the reaction energy barrier. The degree of cyclization reaction caused by simple annealing is limited. Therefore, this scheme introduces zinc salts and elemental sulfur or metal sulfides. On the one hand, it utilizes the zinc ions in the zinc salts to form a new bond with the nitrogen atoms in PAN. On the other hand, the presence of sulfur ions in elemental sulfur or metal sulfides can also react with nitrogen atoms in PAN to form sulfur-nitrogen bonds (CSN), thereby promoting cross-linking between PAN molecular chains and accelerating the cyclization reaction. The appearance of -C=N- on the cyclized PAN makes the PAN surface present a more uniform charge distribution and surface electrostatic potential, so that lithium can be evenly deposited on the electrode surface; more importantly, the zinc salt immobilized on PAN can be converted into ZnO after annealing, and generate Li-Zn alloy during the battery cycle, reducing the reduction potential of lithium ions and promoting lithium desolvation; similarly, S uniformly distributed in PAN fibers in an amorphous form generates Li2S-SEI during the battery cycle, which can effectively isolate the electrolyte and lithium metal, reduce the occurrence of side reactions, and thus reduce the loss of lithium and electrolyte.

[0046] For the mixed solution of PAN, zinc salt, elemental sulfur or metal sulfide, although PAN can be cyclized and ZnO can be generated at the same time by annealing, the product of direct calcination may have uneven cyclization due to the temperature difference between the inside and outside, and the zinc salt cannot be completely converted into ZnO, making it difficult to induce uniform lithium deposition and promote lithium desolvation; on the other hand, the product obtained by direct calcination may have an irregular block structure, which is difficult to load on the electrode surface to protect the electrode. Therefore, by introducing electrospinning technology, PAN, zinc salt, elemental sulfur or metal sulfide is cyclized and ZnO is generated at the same time. The CPAN@ZnO precursor was prepared by electrospinning a mixed solution of metal sulfides, which not only solved the problems of uneven product cyclization and insufficient ZnO formation after direct annealing, but also achieved the control of the density of the CPAN@ZnO layer and the fiber diameter, thereby achieving solid loading on the electrode. At the same time, the CPAN@ZnO precursor prepared by electrospinning had a uniform structure, which laid a good foundation for the subsequent annealing treatment. It should also be mentioned that uniform fiber diameter and appropriate CPAN@ZnO layer density are not easy to obtain, because the uniformity of fiber diameter The degree and density of the membrane are often affected by many factors. The electrospinning push speed, voltage, and collection distance will affect the fiber diameter and the CPAN@ZnO layer arrangement structure at the same time. This scheme controls the electrospinning push speed to 0.6mL / h-1.5mL / h to ensure the continuity of the spinning process and avoid the large diameter difference or breakage caused by too high or too low spinning push speed. On this basis, this scheme further considers the effect of voltage on the fiber diameter and CPAN@ZnO layer structure. By controlling the voltage to 15kV-30kV, this scheme The continuity of the spray droplets was further stabilized, the appearance of beaded structures was avoided, and the deposition of the fibers on the collector was optimized, avoiding the phenomenon of density reduction caused by excessive voltage. Furthermore, this scheme also considered the effect of the collection distance on the fiber diameter and the CPAN@ZnO layer structure. When the collection distance was 15cm-35cm, the fibers had more time to stretch and the solvent to evaporate during flight, thereby optimizing the fiber diameter and further stretching and drying the fibers to form a uniformly structured membrane. When the electrospinning push speed was 0.6mL / h-1.5mL / h, voltage of 15kV-30kV, and collection distance of 15cm-35cm, a CPAN@ZnO precursor with more uniform diameter and density can be obtained. By controlling the fiber diameter and the density of the CPAN@ZnO layer, this scheme can further realize the control of lithium ion flux; on the basis of preparing the CPAN@ZnO precursor by electrospinning, the present invention further anneals the CPAN@ZnO precursor. However, due to the different temperatures of PAN cyclization and zinc salt conversion to ZnO, how to further promote the full conversion of zinc salt on the basis of ensuring the full cyclization of PAN is the difficulty in improving the performance of the CPAN@ZnO layer. This scheme controls the annealing temperature to 140℃-300℃ and the annealing time to 0.1h-2.5h, thereby ensuring the cyclization of PAN and ZnO to the greatest extent. With the help of uniformly distributed zinc salts and elemental sulfur or metal sulfides, PAN is fully cyclized to generate -C=N- groups, so that the prepared CPAN@ZnO obtains uniform charge distribution and surface electrostatic potential, thereby effectively inducing uniform lithium deposition; at the same time, during the annealing process, zinc salts are converted into ZnO, and ZnO is generated into Li-Zn alloy during the cycle process, promoting lithium desolvation; finally, elemental sulfur or metal sulfides, which also play a promoting role in PAN cyclization, also generate amorphous sulfur or sulfur-containing compounds under the action of annealing, and generate Li2S to protect lithium metal after cycling. More interestingly, annealing can further enhance the mechanical properties of CPAN@ZnO precursors, thereby obtaining CPAN@ZnO layers that can induce uniform lithium deposition, inhibit dendrite growth, promote lithium desolvation, and improve battery kinetics and cycle life. .

[0047] As a further solution, in step S1, the molecular weight of PAN is selected from any one of 5w, 8.5w, and 15w.

[0048] As a further solution, in step S1, the mass ratio of PAN, zinc salt, elemental sulfur or metal sulfide is (8-12):(1-6):(0.1-2). When the ratio of PAN, zinc salt, elemental sulfur or metal sulfide satisfies (8-12):(1-6):(0.1-2), it can be ensured that during the annealing process, there are sufficient zinc salts and elemental sulfur or metal sulfides to promote PAN, thereby achieving full cyclization of PAN.

[0049] As some preferred schemes, in step S1, the mass ratio of PAN, zinc salt, elemental sulfur or metal sulfide is (9-11): (2-5): (0.5-2), which helps to optimize the compounding effect among the three, enhance the ability of the CPAN@ZnO layer to promote uniform deposition of lithium, further inhibit dendrite growth, promote desolvation, and thus improve the battery kinetic performance and cycle life.

[0050] As a further solution, the mass ratio of PAN to the organic solvent in step S1 is (4-6): (40-45).

[0051] As a further solution, the zinc salt in step S1 is selected from any one of zinc-based inorganic metal compounds and zinc-based organic metal compounds.

[0052] As a further embodiment, the zinc inorganic metal compound is selected from any one or more of zinc nitrate, zinc phosphate, zinc acetate, zinc silicate, zinc oxide, zinc sulfide, zinc carbonate, zinc chloride, zinc nitrate, zinc sulfate, zinc boric acid, zinc oxide, zinc sulfide, zinc chloride, and zinc hydroxide.

[0053] As a further embodiment, the zinc-based organometallic compound is selected from any one or more of an alkyl zinc compound, an alkoxy zinc compound, an aromatic zinc compound, and a β-diketone zinc compound.

[0054] As a further embodiment, the alkyl zinc compound is selected from any one or more of dimethyl zinc, diethyl zinc, dipropyl zinc, dibutyl zinc, dipentyl zinc, dihexyl zinc, diheptyl zinc, dioctyl zinc, dinonyl zinc and didecyl zinc.

[0055] As a further embodiment, the alkoxy zinc compound is selected from any one or more of methoxy zinc, ethoxy zinc, propoxy zinc, isopropoxy zinc, butoxy zinc, isobutoxy zinc, pentyl zinc, and hexyl zinc.

[0056] As a further embodiment, the aromatic zinc compound is selected from any one or more of diphenyl zinc, p-tolyl zinc, benzimide zinc, naphthyl zinc, diaryl zinc, triphenylphosphine zinc, and benzoyl zinc.

[0057] As a further embodiment, the β-diketone zinc compound is selected from any one or more of zinc di(trifluoroacetylacetone), zinc di(phenylacetylacetone), zinc di(cyclohexylacetylacetone), zinc di(trifluoropropionylacetone), zinc di(ethylacetylacetone), zinc di(benzoylacetone), zinc di(nitroacetylacetone), zinc di(dibenzoylacetone), and zinc acetylacetonate.

[0058] As a further solution, the metal sulfide in step S1 is selected from any one or more of sodium sulfide, potassium sulfide, calcium sulfide, zinc sulfide, aluminum sulfide, lead sulfide, mercuric sulfide, ferrous sulfide, iron sulfide, copper (I) sulfide, copper (II) sulfide, magnesium sulfide, manganese (II) sulfide, nickel (II) sulfide, cadmium sulfide, cobalt (II) sulfide, thallium (I) sulfide, silver sulfide, and barium sulfide.

[0059] As a further solution, in step S1, the organic solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide.

[0060] As a further solution, in step S1, the electrospinning speed is 0.8 mL / h-1.2 mL / h, the collection distance is 20 cm-30 cm, and the voltage is 18 kV-25 kV, which helps to obtain a CPAN@ZnO precursor with a more uniform diameter and a more suitable arrangement, thereby reducing the overpotential and improving the first coulombic efficiency of the battery.

[0061] As a further solution, the thickness of the CPAN@ZnO precursor electrospun in step S1 is selected from 3μm-30μm. By controlling the volume of the mixed solution of PAN, zinc salt, elemental sulfur or metal sulfide, the thickness of the CPAN@ZnO precursor can be accurately controlled, and the thickness of the CPAN@ZnO layer can be further controlled. The volume of the mixed solution of zinc salt, elemental sulfur or metal sulfide is selected from 2mL-10mL. When the thickness of the CPAN@ZnO precursor is selected from 3μm-30μm, it is helpful to construct a CPAN@ZnO layer with excellent mechanical properties, thereby providing a stable environment to induce uniform deposition of lithium, inhibit dendrite growth, and promote lithium desolvation; at the same time, the CPAN@ZnO layer selected from 3μm-30μm also helps to form a CPAN@ZnO layer with moderate density, thereby achieving control of lithium ion flux.

[0062] As a further solution, the volume of the mixed solution of PAN, zinc salt, elemental sulfur or metal sulfide in step S1 is selected from 4 mL to 8 mL, and the thickness of the electrospun CPAN@ZnO precursor is selected from 5 μm to 20 μm.

[0063] As a further solution, in step S2, the annealing atmosphere is air.

[0064] As a further solution, in step S2, the annealing temperature is selected from 240°C-300°C, and the annealing time is selected from 0.5h-2h, which helps to further promote the cyclization of PAN and the formation of ZnO, thereby improving the uniform surface potential and lithium ion binding energy of the CPAN@ZnO layer, and optimizing the battery cycle overpotential.

[0065] This scheme also provides a CPAN@ZnO layer prepared by the above method, with a surface electrostatic potential difference of <0.64KJ / mol and a binding energy greater than 3.5eV, which can induce uniform lithium deposition, inhibit dendrite growth and promote lithium desolvation.

[0066] This solution also provides a battery comprising an electrode modified with a CPAN@ZnO layer, with an interface exchange current density of up to 0.5 mA cm -2-1.5mAcm -2 (like Figure 1 ), cycle life>4500h (such as Figure 2 ), the lithium ion migration number can reach 0.5-0.8 (such as Figure 8 ). The presence of the CPAN@ZnO layer can effectively promote uniform lithium deposition, inhibit dendrite growth and promote lithium desolvation, thereby improving battery kinetics and extending battery cycle life.

[0067] As a further solution, the battery also includes an electrolyte.

[0068] As a further solution, the electrolyte further includes an electrolyte salt, a solvent and an additive.

[0069] As a further embodiment, the solvent is selected from any one of ether solvents, ester solvents and sulfone solvents.

[0070] As a further embodiment, the ether solvent is selected from dioxolane, oxidized methyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, polyethylene glycol dimethyl ether, ethylene glycol methyl ether ethyl ether, ethylene glycol diethyl ether, diethylene glycol methyl ether ethyl ether, diethylene glycol diethyl ether, triethylene glycol methyl ether ethyl ether, triethylene glycol diethyl ether, tetraethylene glycol methyl ether ethyl ether, tetraethylene glycol diethyl ether, ethylene glycol methyl ether propyl ether, ethylene glycol ethyl ether propyl ether, ethylene glycol dipropyl ether, diethylene glycol methyl ether propyl ether, diethylene glycol ethyl ether propyl ether, diethylene glycol dipropyl ether, triethylene glycol methyl ether propyl ether, triethylene glycol dipropyl ether, tetraethylene glycol methyl ether propyl ether, tetraethylene glycol ethyl ether propyl ether, At least one of propyl ether, ethylene glycol methyl ether butyl ether, ethylene glycol ethyl ether butyl ether, ethylene glycol propyl ether butyl ether, ethylene glycol dibutyl ether, diethylene glycol methyl ether butyl ether, diethylene glycol ethyl ether butyl ether, diethylene glycol propyl ether butyl ether, diethylene glycol dibutyl ether, triethylene glycol methyl ether butyl ether, triethylene glycol ethyl ether butyl ether, triethylene glycol propyl ether butyl ether, triethylene glycol dibutyl ether, tetraethylene glycol methyl ether butyl ether, tetraethylene glycol ethyl ether butyl ether, tetraethylene glycol propyl ether butyl ether, and tetraethylene glycol dibutyl ether is selected as a further embodiment, and the ester solvent is selected from any one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl acetate, ethyl acetate, butyl acetate, ethyl propionate, and methyl propionate.

[0071] As a further embodiment, the sulfone solvent is selected from any one or more of 1,1,2,2-tetramethyl sulfoxide, dimethyl sulfoxide, diethyl sulfoxide, methyl ethyl sulfone, dimethyl sulfone, trimethyl sulfone, methylsulfonylmethane, ethyl sulfoxide, propyl sulfoxide, methyl sulfoxide, ethyl methyl sulfone, and hydroxyethyl sulfone.

[0072] As a further embodiment, the electrolyte salt is selected from an organic electrolyte salt and an inorganic electrolyte salt.

[0073] As a further solution, the organic electrolyte salt is selected from at least one of sodium sulfonimide salt and lithium sulfonate.

[0074] As a further embodiment, the sulfonyl imide lithium salt is selected from at least one of bis(trifluoromethanesulfonyl)imide lithium, fluoroboron bis(trifluoromethylsulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium, bis(trifluoroethanesulfonyl)imide lithium, bis(bisfluorosulfonyl)imide lithium, bis(perfluorobutanesulfonyl)imide lithium, bis(fluoromethanesulfonyl)imide lithium, bis(difluoroethanesulfonyl)imide lithium, bis(hexafluorosulfonyl)imide lithium, bis(trifluoromethoxysulfonyl)imide lithium, and bis(tetrafluorobutanesulfonyl)imide lithium.

[0075] As a further embodiment, the lithium sulfonate salt is selected from at least one of lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, lithium butanesulfonate, lithium pentanesulfonate, lithium hexanesulfonate, lithium p-toluenesulfonate and lithium benzenesulfonate.

[0076] As a further solution, the inorganic electrolyte salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium fluorosulfonyl imide, lithium chloride, lithium nitrate, lithium sulfate, lithium oxide, lithium iodide, lithium fluoride, and lithium bromide.

[0077] As a further solution, the additive is selected from at least one of ethylene methyl carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, trimethyl phosphate, lithium nitrate, 1,3-propane sultone, tripropyl phosphate, succinonitrile, and fluorosulfonyl imide lithium salt.

[0078] As some preferred solutions, the electrolyte formula can be: dioxolane:dimethoxyethane volume ratio of 1:1, 1M lithium bis(trifluoromethanesulfonyl)imide, 5wt% lithium nitrate.

[0079] As some preferred solutions, the electrolyte formula can be a 1:1 volume ratio of fluoroethylene carbonate: methyl vinyl carbonate, 1M lithium hexafluorophosphate.

[0080] As some preferred solutions, the electrolyte formula can be a volume ratio of trimethyl sulfone:fluoroethylene carbonate of 8:2, 1M lithium bis(trifluoromethanesulfonyl)imide.

[0081] As some preferred schemes, the electrolyte formula can be a volume ratio of dimethoxyethane: methyl ether oxide: tetrafluoroethane of 1:1:1, 1.5M lithium bis(fluorosulfonyl)imide.

[0082] As a further solution, the battery can be any one of a lithium metal, sodium metal, and potassium metal battery.

[0083] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0084] The chemical raw materials involved in the following examples and comparative examples are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and limitations.

[0085] Example 1

[0086] Preparation of CPAN@ZnO layer

[0087] S1: 1 g of PAN with a weight average molecular weight of 8W, 0.4 g of Zn(Ac)2 and 0.2 g of sulfur powder were dissolved in 10 g of N,N-dimethylformamide, and then electrospun at a voltage of 20 kV, with an electrospinning speed of 1 mL / h and a collection distance of 25 cm to obtain a CPAN@ZnO precursor with a layer thickness of 10 μm;

[0088] S2: The CPAN@ZnO precursor was annealed at 280 °C for 1 h to obtain the CPAN@ZnO layer.

[0089] The CPAN@ZnO layer was respectively attached to the Li foil and the Cu foil, and roller pressed to obtain the Li electrode and Cu electrode modified by the CPAN@ZnO layer.

[0090] Preparation of Li||Li battery

[0091] The Li electrode modified with CPAN@ZnO layer was used as the positive electrode and negative electrode, and was assembled in the order of positive electrode, separator, and negative electrode. Then, the electrolyte (DOL / DME (1:1, vol), 1M LiPF6, 5wt% LNO) was injected, and the Li||Li battery was obtained after vacuum packaging, standing, and formation.

[0092] Preparation of Li||Cu battery

[0093] A Cu electrode modified with a CPAN@ZnO layer was used as the negative electrode, and an unmodified lithium sheet was used as the positive electrode. The positive electrode, the separator, and the negative electrode were assembled in order, and then the electrolyte (DOL / DME (1:1, vol), 1M LiPF6, 5wt% LNO) was injected. After vacuum packaging, standing, and formation, a Li||Cu battery was obtained.

[0094] Preparation of Li||811 battery

[0095] Li||811 was used as the positive electrode, and a Li electrode modified with a CPAN@ZnO layer was used as the negative electrode. The positive electrode, the separator, and the negative electrode were assembled in order, and then the electrolyte (DOL / DME (1:1, vol), 1M LiPF6, 5wt% LNO) was injected. After vacuum packaging, standing, and formation, a Li||811 battery was obtained.

[0096] Example 2

[0097] The preparation method and steps are the same as those in Example 1, except that the amount of Zn(Ac)2 used is 0.2 g.

[0098] Example 3

[0099] The preparation method and steps are the same as those in Example 1, except that the amount of Zn(Ac)2 used is 0.5.

[0100] Example 4

[0101] The preparation method and steps are the same as those in Example 1, except that the amount of PAN used is 1.1 g.

[0102] Example 5

[0103] The preparation method and steps are the same as those in Example 1, except that the amount of PAN used is 0.9 g.

[0104] Example 6

[0105] The preparation method and steps are the same as those in Example 1, except that the amount of sulfur powder used is 0.05 g.

[0106] Example 7

[0107] The preparation method and steps are the same as those in Example 1, except that the weight average molecular weight of PAN is 15w.

[0108] Example 8

[0109] The preparation method and steps are the same as those in Example 1, except that the weight average molecular weight of PAN is 5w.

[0110] Example 9

[0111] The preparation method and steps are the same as those in Example 1, except that the electrospinning speed is 0.8 mL / h, the voltage is 25 kV, and the collection distance is 20 cm.

[0112] Example 10

[0113] The preparation method and steps are the same as those in Example 1, except that the electrospinning speed is 1.2 mL / h, the voltage is 18 kV, and the collection distance is 30 cm.

[0114] Embodiment 11

[0115] The preparation method and steps are the same as those in Example 1, except that the thickness of the CPAN@ZnO precursor is 5 μm.

[0116] Example 12

[0117] The preparation method and steps are the same as those in Example 1, except that the thickness of the CPAN@ZnO precursor is 20 μm.

[0118] Example 13

[0119] The preparation method and steps are the same as those in Example 1, except that the annealing time and temperature are 0.5 h and 240° C. respectively.

[0120] Embodiment 14

[0121] The preparation method and steps are the same as those in Example 1, except that the annealing time and temperature are 2 h and 300° C., respectively.

[0122] Comparative Example 1

[0123] Li||Li batteries were prepared using unmodified Li electrodes as positive and negative electrodes;

[0124] The Li||Cu battery was prepared by using an unmodified lithium sheet as the positive electrode sheet and an unmodified Cu electrode as the negative electrode sheet;

[0125] Li||811 batteries were prepared using NCM811 as the positive electrode and unmodified Li electrode as the negative electrode.

[0126] Comparative Example 2

[0127] The preparation method and steps are the same as those in Example 1, except that polyvinyl pyrrolidone is used to replace PAN.

[0128] Comparative Example 3

[0129] The preparation method and steps are the same as those in Example 1, except that sulfur powder is not added.

[0130] Comparative Example 4

[0131] The preparation method and steps are the same as those in Example 1, except that Zn(Ac)2 is not added

[0132] Comparative Example 5

[0133] The preparation method and steps are the same as those in Example 1, except that the CPAN@ZnO precursor is prepared by a blade coating method. The preparation method is as follows: a mixed solution of PAN, Zn(Ac)2 and sulfur powder is poured into a coating tank of a coating machine, the ceramic blade gap is adjusted to 30 μm, the coating speed is 0.1 nm / s, and the coating pressure is 500 grams-force to obtain a CPAN@ZnO precursor.

[0134] Comparative Example 6

[0135] The preparation method and steps are the same as those in Example 1, except that the electrospinning push speed is 0.1 mL / h, the voltage is 10 kV, and the collection distance is 10 cm.

[0136] Comparative Example 7

[0137] The preparation method and steps are the same as those in Example 1, except that the electrospinning speed is 2 mL / h, the voltage is 40 kV, and the collection distance is 40 cm.

[0138] Comparative Example 8

[0139] The preparation method and steps are the same as those in Example 1, except that no annealing is performed.

[0140] Comparative Example 9

[0141] The preparation method and steps are the same as those in Example 1, except that the annealing temperature is 320° C. and the annealing time is 1 h.

[0142] Comparative Example 10

[0143] The preparation method and steps are the same as those in Example 1, except that the annealing temperature is 120° C. and the annealing time is 1 h.

[0144] Comparative Example 11

[0145] The preparation method and steps are the same as those in Example 1, except that the annealing temperature is 320° C. and the annealing time is 3 h.

[0146] Test method:

[0147] (1) Li||Li battery cycle test

[0148] After the prepared Li||Li battery was left to stand for 8 hours, a 0.5 mA / cm 2 The current density is constant current discharge to 1 mAh / cm 2 , then 0.5 mA / cm 2 The current density is charged to 1 mAh / cm 2 Cut off, carry out cycle test, and obtain lithium deposition overpotential.

[0149] (2) First Coulombic efficiency of Li||Cu battery

[0150] After the prepared Li||Cu battery was left to stand for 8 hours, a 0.5 mA / cm 2 The current density is constant current discharge to 1 mAh / cm 2 , let stand for 1 minute, then use 0.5mA / cm 2 The current density is constant current charged to 1V cutoff.

[0151] (3) Li||811 battery 0.5C cycle 200 times

[0152] First, charge at a rate of 0.5C to 4.3V, let stand for 1 minute, and then discharge at a rate of 0.5C to 2.8V. This is considered a cycle. After 200 cycles, the capacity retention rate is tested and calculated.

[0153] (4) Li||811 battery 1C cycle 100 times

[0154] First, charge at a rate of 1C to 4.3V, let stand for 1 minute, and then discharge at a rate of 1C to 2.8V. This is considered a cycle. After 100 cycles, the capacity retention rate is tested.

[0155] The first coulombic efficiency of Li||Cu battery = the charge specific capacity of the first cycle / the discharge specific capacity × 100%.

[0156] Capacity retention rate = (specific capacity of the last cycle / specific capacity of the first cycle) × 100%.

[0157] The test results of Examples 1-14 and Comparative Examples 1-11 are shown in Table 2.

[0158] Table 1

[0159]

[0160]

[0161]

[0162]

[0163] Table 2

[0164]

[0165]

[0166]

[0167] It can be observed from Examples 1-14 and Comparative Examples 1-11 that Examples 1-14 as a whole present a uniform surface electrostatic potential, lithium ion binding energy, and better battery cycle overpotential, first coulombic efficiency, specific capacity, and capacity retention rate that are far superior to Comparative Examples 1-11.

[0168] From the comparison between Example 1 and Comparative Example 1, it can be seen that when the CPAN@ZnO layer modified electrode proposed in this scheme is not used, the comprehensive performance of Comparative Example 1 is far lower than that of Example 1 ( Figure 1-3), indicating that the CPAN@ZnO layer is of great significance in inducing uniform lithium deposition, inhibiting dendrite growth, promoting lithium desolvation, and improving battery kinetics and cycle life.

[0169] From Example 1 and Comparative Examples 2-4, it can be observed that whether it is PAN, zinc salt, or elemental sulfur or metal sulfide, it is necessary for the three to be compounded to construct the CPAN@ZnO layer, to achieve the induction of uniform lithium deposition, to promote lithium desolvation, and to inhibit the growth of dendrites. When PAN is replaced with polyvinyl pyrrolidone (Comparative Example 2), due to the lack of -CN, polyethylene cannot induce uniform lithium deposition like PAN. Therefore, the uniform surface electrostatic potential and lithium ion binding energy of Comparative Example 2 are far inferior to those of Example 1, and further lead to a decrease in the battery capacity retention rate. When sulfur powder is not added (Comparative Example 3), the lack of the assistance of sulfur powder, on the one hand, PAN cannot be fully cyclized during the annealing process, resulting in the uniform surface electrostatic potential and lithium ion binding energy being affected, and by Figure 4 It can be observed that the CPAN@ZnO layer prepared in Example 1 has a more uniform surface electrostatic potential (<0.2KJ / mol) and a higher binding energy (>4.21eV); on the other hand, in Comparative Example 3 without adding sulfur powder, Li2S cannot be formed to separate the electrolyte and lithium metal during the cycle, resulting in the cycle performance being affected. Figure 5 , Figure 6 as well as Figure 7 (B), the presence of ZnO can be clearly observed in Example 1 to which Zn(Ac)2 is added ( Figure 5 The presence of ZnO characteristic peaks was observed in Figure 6 The appearance of ZnO was observed in Figure 7 The white dots in (B) are ZnO), indicating that zinc salts represented by Zn(Ac)2 can generate ZnO through annealing. However, when zinc salts are not added (Comparative Example 4), Comparative Example 4 lacking ZnO cannot generate Li-Zn alloy during cycling, which reduces the lithium ion reduction potential and affects lithium desolvation. Therefore, the overpotential of the Li||Li battery cycled for 100h is 0.047eV, which is much higher than that of Example 1. In addition, Figure 6 It can be observed that the addition of zinc salt is also beneficial to promote the cyclization of PAN. Therefore, it can be seen that the combination of PAN, zinc salt and elemental sulfur or sulfide is of great significance for achieving uniform lithium deposition, promoting lithium desolvation, and inhibiting the growth of dendrites.

[0170] Example 1 and Comparative Example 5 show the effect of electrospinning on the performance of the CPAN@ZnO layer. When the CPAN@ZnO layer was prepared by the blade coating method, the comprehensive performance of Comparative Example 5 was significantly inferior to that of Example 1. This may be because although the blade coating method can also prepare the CPAN@ZnO layer, the CPAN@ZnO layer prepared by electrospinning has a microscopic arrangement that is more suitable for batteries. Therefore, compared with Comparative Example 5, Example 1 prepared by electrospinning has better performance.

[0171] In the operation of electrospinning, the diameter of the fiber and the density of the membrane are often determined by the push speed and voltage of the electrospinning. Therefore, it can be observed from Example 1 and Comparative Examples 6-7 that when electrospinning is performed at a push speed of 0.1 mL / h and a voltage of 10 kV (Comparative Example 6), the prepared CPAN@ZnO layer exhibits an overpotential much higher than that of Example 1 and a lithium ion binding energy much lower than that of Example 1. This may be because the CPAN@ZnO layer prepared using the spinning conditions of Comparative Example 6 has finer fibers and a sparser membrane structure, which cannot provide a uniform and dense matrix for subsequent annealing. At the same time, the fine fibers and sparse membrane structure may not be able to achieve the regulation of lithium ion flux. Therefore, the performance of Example 1 is much better than that of Comparative Example 6. Similarly, Comparative Example 7 also has similar problems. When the electrospinning speed and voltage are increased, on the one hand, the prepared fibers may be uneven. At the same time, it may also cause the fibers to be arranged too tightly, resulting in increased resistance and increased overpotential, while affecting the uniform surface potential and lithium ion binding energy. Therefore, according to Example 1, Comparative Examples 6-7, the electrospinning speed is selected to be 0.6mL / h-1.5mL / h, and the voltage is 15kV-30kV.

[0172] Through annealing, PAN generates ZnO and amorphous sulfur while achieving cyclization, thereby achieving uniform lithium deposition, inhibiting dendrite growth, and promoting lithium desolvation. Therefore, annealing is crucial for the formation of CPAN@ZnO layer. It can be observed from Comparative Example 8 that ( Figure 6 ), when no annealing is performed, the peak intensity of -C≡N on Comparative Example 8 is significantly stronger than -C=N-, while the peak intensity of -C=N- in Example 1 which is annealed is significantly stronger than -C≡N, indicating that annealing promotes the cyclization of PAN; in addition, the operation without annealing may also make it difficult for zinc salt to be converted into ZnO, so the complexing effect between PAN, ZnO and sulfur powder cannot be fully exerted, thereby affecting the overall performance of Comparative Example 8. When no annealing is performed, the overpotential of the Li||Li battery after 100h of cycling is 0.047eV, and the uniform surface potential, lithium ion binding ability and cycle capacity retention rate are also much weaker than those in Example 1.

[0173] The annealing temperature and time are also important factors affecting the performance of the CPAN@ZnO layer. Generally speaking, extending the annealing time and increasing the annealing temperature can give the CPAN@ZnO layer electrical conductivity. However, the improvement of electrical conductivity does not mean that the CPAN@ZnO layer promotes uniform lithium deposition, desolvation and improves the ability to inhibit dendrite growth. On the contrary, the improvement of electrical conductivity may lead to battery self-discharge and local short circuit, and affect the ability of the CPAN@ZnO layer itself. It can be observed from Example 1 and Comparative Examples 9-10 that increasing the carbonization temperature and extending the carbonization time can improve the performance of the CPAN@ZnO layer. The uniform surface potential, lithium ion binding energy and cycle overpotential of the nO layer are significantly affected. When the annealing temperature is increased to 320°C (Comparative Examples 9 and 11), the battery cycle overpotential increases, and the ability to induce uniform lithium ion deposition deteriorates. When the annealing time is shortened and the annealing temperature is lowered (Comparative Example 10), it may lead to uneven PAN cyclization, the zinc salt cannot be fully converted into ZnO, and the sulfur powder is difficult to be converted into amorphous sulfur, thereby affecting the performance of the CPAN@ZnO layer. According to Example 1 and Comparative Examples 9-11, the annealing time and temperature are selected from 0.1h-2.5h and 140°C-300°C.

[0174] Examples 1-6 discuss the effect of the ratio of PAN, zinc salt, elemental sulfur or metal sulfide in S1 on the performance of the CPAN@ZnO layer. It can be observed from Example 2 that when the ratio of the three is 5:1:1, the overpotential (0.01V) of the Li||Li battery in Example 1 after 100h of cycling is better than the overpotential (0.015V) of the Li||Li battery in Example 2 after 100h of cycling. This may be because the zinc salt content in Example 1 is more sufficient than that in Example 2, so a higher content of ZnO can be converted, thereby optimizing the overpotential. In Example 3, the ratio of the three is 10:5:2, and the overpotential of Example 1 is still better than that of Example 2. This may be because Example 1 has a more suitable zinc salt content than Example 3, which can maximize the effect of ZnO.

[0175] Examples 4-5 discuss the effect of changing the PAN content in the ratio of the three on the performance of the CPAN@ZnO layer. It can be observed from Examples 1 and 4-5 that Example 1 has the best performance. This may be because when the ratio of the three is 5:2:1, the ratio of zinc salt and sulfur powder can promote PAN cyclization to the greatest extent, thereby optimizing the uniform surface potential (0.2 KJ / mol) and binding energy with lithium ions (4.21 eV) of Example 1, so Example 1 exhibits the best performance.

[0176] Examples 1 and 6 demonstrate the effect of the sulfur powder ratio on the performance of the CPAN@ZnO layer. It can be observed from Examples 1 and 6 that when the ratio of the three is 5:2:1, Example 1 exhibits better cycle ability. This may be because when the sulfur powder content in Example 1 is higher, a higher content of Li2S protective electrode can be generated during the cycle, thereby improving the cycle ability of the battery.

[0177] Therefore, according to Examples 1-6, the preferred ratio of PAN, zinc salt, and sulfide is (9-11): (2-5): (0.5-2).

[0178] Examples 1, 7-8 demonstrate the effect of PAN weight average molecular weight on the performance of CPAN@ZnO layer. When the PAN weight average molecular weight is selected from 8w, Example 1 exhibits better performance. This may be because when the PAN weight average molecular weight is 8w, on the one hand, it can achieve better compounding with zinc salt and elemental sulfur or metal sulfide, thereby forming a more fully cyclized CPAN@ZnO layer and improving the ability to induce uniform lithium deposition. At the same time, when the PAN weight average molecular weight is selected from 8w, it can also form a more stable and dense CPAN@ZnO layer under the action of annealing, thereby improving the battery cycle performance.

[0179] Examples 1, 9-10 further discuss the role of electrospinning push speed and voltage. When the push speed is 1 mL / h and the voltage is 20 kV, Figure 7 (B) From the SEM image of Example 1, it can be observed that the fibers prepared under the conditions of a pushing speed of 1 mL / h and a voltage of 20 kV exhibit a uniform nanofiber structure, and the fiber diameter is about 300 nm. Compared with Examples 9-10, Example 1 exhibits better overall performance. This may be because the CPAN@ZnO layer prepared at a pushing speed of 1 mL / h and a voltage of 20 kV has a more uniform and dense structure, which can provide a more uniform CPAN@ZnO layer matrix for subsequent annealing. At the same time, meeting the pushing speed of 1 mL / h and the voltage of 20 kV can also obtain a CPAN@ZnO layer with a better arrangement structure, thereby further realizing the control of lithium ion flux.

[0180] For the SEI layer, changes in thickness will bring about changes in performance, so it is necessary to test the thickness of the CPAN@ZnO layer. It can be observed from Examples 1, 11, and 12 that Example 1 has a better Li||Li battery cycle 100h overpotential (0.01V) and the ability to induce lithium ion deposition. At the same time, whether it is cycled at 0.5C for 200 weeks or 1C for 100 weeks, Example 1 shows better specific capacity and capacity retention rate. This may be because Example 1 with a thickness of 10μm can minimize the influence of resistance while ensuring the stability of the CPAN@ZnO layer, thereby improving battery performance. Therefore, based on Examples 1, 11, and 12, the preferred CPAN@ZnO layer thickness is 5μm-20μm.

[0181] Optimizing the combination of annealing temperature and annealing time is helpful to further obtain a CPAN@ZnO layer with better performance. It can be seen from Examples 1, 13, and 14 that when the annealing temperature is 280°C and the annealing time is 1h, Example 1 exhibits the best performance. This may be because the annealing time of 1h and annealing at 280°C can achieve the maximum degree of cyclization of PAN and fully convert the zinc salt into ZnO. In addition, the CPAN@ZnO layer that meets the annealing conditions of Example 1 can further improve the mechanical properties of the CPAN@ZnO layer matrix under the action of annealing. Therefore, Example 1 exhibits better uniform surface electrostatic potential, lithium ion binding ability, and battery cycle overpotential and cycle capacity for 100h than Examples 13 and 14.

[0182] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.

Claims

1. A method for preparing a CPAN@ZnO layer, characterized in that: The steps include: S1: According to the stoichiometric ratio, PAN, zinc salt, elemental sulfur or metal sulfide are dissolved in an organic solvent in sequence, and electrospinning is performed at a voltage of 15kV-30kV, the electrospinning push speed is 0.6mL / h-1.5mL / h, and the collection distance is 15cm-35cm to obtain a CPAN@ZnO precursor; S2: Annealing the CPAN@ZnO precursor at 140°C-300°C for 0.1h-2.5h to obtain a CPAN@ZnO layer.

2. The method for preparing the CPAN@ZnO layer according to claim 1, characterized in that: In step S1, the molecular weight of PAN is selected from any one of 5w, 8.5w, and 15w; Preferably, in step S1, the mass ratio of PAN, zinc salt, elemental sulfur or metal sulfide is (8-12): (1-6): (0.1-2); Preferably, in step S1, the mass ratio of PAN, zinc salt, elemental sulfur or metal sulfide is (9-11): (2-5): (0.5-2); Preferably, in step S1, the mass ratio of PAN to the organic solvent is (4-6): (40-45).

3. The method for preparing the CPAN@ZnO layer according to claim 1, characterized in that: In step S1, the zinc salt is selected from any one of zinc inorganic metal compounds and zinc organic metal compounds; Preferably, the zinc-based organometallic compound is selected from any one or more of an alkyl zinc compound, an alkoxy zinc compound, an aromatic zinc compound, and a β-diketone zinc compound.

4. The method for preparing the CPAN@ZnO layer according to claim 1, characterized in that: In step S1, the metal sulfide is selected from any one or more of sodium sulfide, potassium sulfide, calcium sulfide, zinc sulfide, aluminum sulfide, lead sulfide, mercuric sulfide, ferrous sulfide, iron sulfide, copper (I) sulfide, copper (II) sulfide, magnesium sulfide, manganese (II) sulfide, nickel (II) sulfide, cadmium sulfide, cobalt (II) sulfide, thallium (I) sulfide, silver sulfide, and barium sulfide.

5. The method for preparing the CPAN@ZnO layer according to claim 1, characterized in that: In the step S1, the organic solvent is selected from one or more of dimethyl sulfoxide, N,N-dimethylformamide, N-methylpyrrolidone, and N,N-dimethylacetamide.

6. The method for preparing the CPAN@ZnO layer according to claim 1, characterized in that: In the step S1, the electrospinning pushing speed is 0.8 mL / h-1.2 mL / h, the collection distance is 20 cm-30 cm, and the voltage is 18 kV-25 kV; Preferably, the thickness of the electrospun CPAN@ZnO precursor in step S1 is controlled by a mixed solution of PAN, zinc salt, elemental sulfur or metal sulfide, the volume of the mixed solution of zinc salt, elemental sulfur or metal sulfide is selected from 2mL-10mL, and the thickness of the CPAN@ZnO precursor is selected from 3μm-30μm; Preferably, the volume of the mixed solution of PAN, zinc salt, elemental sulfur or metal sulfide is selected from 4 mL to 8 mL, and the thickness of the electrospun CPAN@ZnO precursor is selected from 5 μm to 20 μm.

7. The method for preparing the CPAN@ZnO layer according to claim 1, characterized in that: In step S2, the annealing atmosphere is air; Preferably, in step S2, the annealing temperature is selected from 240° C.-300° C., and the annealing time is selected from 0.5 h-2 h.

8. An electrode modified by a CPAN@ZnO layer, characterized in that: The electrode is modified with a CPAN@ZnO layer prepared by any one of the methods of claim 1 to claim 7, and the surface electrostatic potential difference of the electrode modified with the CPAN@ZnO layer is less than 0.64 KJ / mol, and the binding energy is greater than 3.5 eV.

9. A battery comprising an electrode modified with a CPAN@ZnO layer, characterized in that: Contains electrodes modified with a CPAN@ZnO layer.

10. A battery comprising an electrode modified with a CPAN@ZnO layer according to claim 9, characterized in that: The lithium ion migration number of the battery can reach 0.5-0.8, and the interface exchange current density of the battery can reach 0.5-1.5mAcm -2 , the battery cycle life>4500h; Preferably, the battery comprising the electrode modified with the CPAN@ZnO layer further comprises an electrolyte; Preferably, the electrolyte further comprises an electrolyte salt, a solvent and an additive; Preferably, the solvent is selected from any one of ether solvents, ester solvents, and sulfone solvents; Preferably, the electrolyte salt is selected from organic electrolyte salts and inorganic electrolyte salts; Preferably, the organic electrolyte salt is selected from at least one of sodium sulfonimide salt and lithium sulfonate.

Citation Information

Patent Citations

  • Novel ester electrolyte suitable for rapid charging of lithium metal battery

    CN118281317A